Synergistic modulation of gut microbiota and mindfulness-based interventions in schizophrenia: Integrating neurotransmitter regulation and multimodal therapeutic strategies - Zajkowska, Izabela; Niczyporuk, Patrycja; Giba, Aleksandra; Iłendo, Kamila; Królikiewicz, Wiktor; Marecki, Rafał; Kicman, Aleksandra (Quality in Sport, 2025)
This review explores an innovative, integrative therapeutic approach that combines probiotics, prebiotics, and mindfulness-based interventions (MBIs) to target the dysregulation of the gut–brain axis in schizophrenia. The rationale for this combined strategy is rooted in the overlapping mechanisms by which both biological and psychosocial interventions influence neurophysiological processes. Probiotics and prebiotics are shown to rebalance the gut microbiota, thereby enhancing the synthesis of key neurotransmitters—such as serotonin, gamma-aminobutyric acid (GABA), and dopamine—and reducing systemic inflammation and oxidative stress. In parallel, MBIs, including Mindfulness-Based Stress Reduction (MBSR) and Mindfulness-Based Cognitive Therapy (MBCT), promote improvements in emotional regulation, cognitive function, and neuroplasticity through the modulation of neurophysiological pathways, notably by attenuating amygdala reactivity and heightening prefrontal cortex engagement. Viewing these interventions through the unifying lens of the gut–brain axis presents a promising paradigm: both modalities may exert synergistic effects to support the management of persistent symptoms of schizophrenia and complement existing therapeutic approaches. By converging on shared biological and psychosocial pathways, this integrative model could offer a more comprehensive strategy for addressing the multifaceted challenges of schizophrenia. While preliminary evidence is encouraging, further controlled clinical studies are essential to determine optimal treatment protocols and to elucidate the precise mechanisms by which these therapies interact to enhance patient outcomes.